Application of Recombinant Gnathostoma spinigerum Matrix Metalloproteinase-Like Protein for Serodiagnosis of Human Gnathostomiasis by Immunoblotting - Penchom Janwan (2018)
Matrix metalloproteinase (MMPs) is the extracellular zinc-dependent endopeptidase and is secreted for degrading extracellular matrix molecules of host tissues. A cDNA encoding MMP-like protein of Gnathostoma spinigerum larvae was amplified by reverse transcription-polymerase chain reaction, and was cloned into a prokaryotic expression vector, and expressed in Escherichia coli. Total immunoglobulin G class (total IgG) antibody responses to the recombinant MMP-like protein were analyzed by immunoblot diagnosis of human gnathostomiasis. Serum samples from proven and clinically suspected cases of gnathostomiasis, other parasitic diseases patients, and from healthy volunteers were tested. The immunoblotting gave high sensitivity (100%) and specificity (94.7%). Positive and negative predictive values were 85.4% and 100%, respectively. Recombinant MMP-like protein can be used as a diagnostic antigen and potentially replace native parasite antigens to develop a gnathostomiasis diagnostic kit.© 2013 by The American Society of Tropical.